Presidential economic narratives in Indonesia: A multimodal critical discourse analysis - Emha, Ratna Juwitasari; Mubarok, Yasir (Journal of Research on English and Language Learning (J-REaLL), 2026)
Political discussions often present economic performance as a success story, even when broader social and economic conditions suggest otherwise. In presidential budget speeches, statistics are frequently used to demonstrate success and build public trust. However, the ideological and persuasive functions of numbers, especially when combined with visual elements, remain underexplored. Most existing studies focus primarily on spoken or written language, offering limited insight into how numerical data and visuals work together to legitimize economic policies. This study examines the 2026 state budget address delivered by the President of the Republic of Indonesia using multimodal critical discourse analysis (MCDA). It investigates how verbal and visual resources interact to construct a persuasive narrative portraying the government as competent, welfare-oriented, and committed to national development. The findings reveal that economic statistics and visual symbols are not neutral representations of reality but are strategically employed to justify political authority. Through verbal strategies such as implication, repetition, and selective omission, alongside visual elements including iconography, setting, and salience, the speech constructs a narrative of economic success while marginalizing deeper social and economic issues. Among the visual strategies identified, salience emerges as the most dominant, with images consistently positioning the President as the central authority figure. Generally, the study demonstrates how numbers, repetition, and selective presentation operate together with nationalist and power-related imagery to shape public perception. These findings highlight how data presentation can influence public trust, reduce transparency, and ultimately affect democratic accountability in political and economic communication.